AB0955 Tildrakizumab efficacy over time by week 28 response levels in two phase 3 clinical trials in patients with chronic plaque psoriasis. (12th June 2018) - Blauvelt, A.; Sofen, H.; Papp, K.; Gooderham, M.; Zhao, Y.; Lowry, S.; Mendelsohn, A.; Parno, J.; Li, Q.; Rosa, C.L.; Reich, K.
Abstract : Background: Tildrakizumab (TIL), a high affinity, humanised, IgG1/κ monoclonal antibody for IL-23p19, recently demonstrated efficacy in patients with chronic plaque psoriasis in two, phase 3 clinical trials. Objectives: To examine efficacy from baseline to week 52 among TIL patients achieving various Psoriasis Area and Severity Index (PASI) responses at week 28. Methods: ReSURFACE 1 (NCT01722331 ) and reSURFACE 2 (NCT01729754 ) were double-blind, randomised controlled trials in subjects with moderate-to-severe chronic plaque psoriasis 1 . Part 1 (0–12 weeks) was placebo controlled; Part 2 (12–28 weeks) re-randomised placebo patients to TIL; Part 3 (28–64 weeks, reSURFACE 1; 28–52 weeks, reSURFACE 2) patients with ≥PASI 50 were re-randomised to continue or increase TIL dose or to placebo based on response at week 28. In this post-hoc pooled analysis, patients on TIL 100 mg and 200 mg from baseline to week 52 were classified in 5 mutually exclusive groups based on their week-28 PASI response: PASI <50, PASI 50–74, PASI 75–89, PASI 90–99, and PASI 100. Baseline characteristics and% PASI improvement from baseline up to week 52 (observed data) were examined for each group. Results: This analysis included 575 (TIL 100 mg) and 581 (TIL 200 mg) patients; the overall pooled Week 28 PASI 75/90/100 responses were 77%/54%/23% (TIL 100 mg) and 78%/58%/29% (TIL 200 mg). At week 28, 133 (23.1%), 175 (30.4%), 137 (23.8%), 82 (14.3%), and 48 (8.3%) TIL 100 mg patients and 170 (29.3%), 169 (29.1%), 114 (19.6%), 105 (18.1%), and 23 (4.0%) TIL 200 mg achieved PASI 100, PASI 90–99, PASI 75–89, PASI 50–74, and PASI <50, respectively. On average, PASI 100 patients were younger, lighter, and had shorter disease duration at baseline compared to other response groups. For TIL 100 mg, % PASI improvement was highest for PASI 100 and least for PASI <50 patients for all visits up to week 28 (week 4: 53%, 46%, 38%, 30%, and 16%; week 28: 100%, 95%, 83%, 64%, and 33% for PASI 100, PASI 90–99, PASI 75–89, PASI 50–74, and PASI <50 categories, respectively). Among patients achieving PASI >50 at week 28 and continued up to 52 weeks, % PASI improvement remained consistent or improved from week 28 to week 52. Similar results were observed for TIL 200 mg as well as subgroup analysis with bio-naive and bio-experienced patients, respectively. Conclusions: The majority of TIL 100 and 200 mg patients achieved PASI>50 response at week 28, and PASI improvement was maintained from week 28 to week 52. Among patients achieving ≥PASI 90 at week 28, TIL 100 and 200 mg were associated with rapid improvement by week 4. Disclosure of Interest: A. Blauvelt Grant/research support from: AbbVie, Amgen, Boehringer Ingelheim, Celgene, Dermira, Genentech, GSK, Janssen, Lilly, Merck and Co, Novartis, Pfizer, Regeneron, Sandoz, Sanofi Genzyme, Sun, UCB, and Valeant, Consultant for: AbbVie, Amgen, Boehringer Ingelheim, Celgene, Dermira, Genentech, GSK, Janssen, Lilly, Merck and Co, Novartis, Pfizer, Regeneron, Sandoz, Sanofi Genzyme, Sun, UCB, and Valeant, Speakers bureau: Eli Lilly, H. Sofen Grant/research support from: Boehringer-Ingelheim, Novartis, Pfizer, Janssen, Lilly, Amgen, and Merck and Co., Inc., Consultant for: Novartis, Janssen, and Eli Lilly, Speakers bureau: Novartis, Janssen, and Eli Lilly, K. Papp Grant/research support from: Amgen, Anacor, AbbVie, Active Biotech, Allergan, Astellas, AstraZeneca, Basilea, Bayer, Biogen-Idec, BMS, Boehringer-Ingelheim, CanFite, Celgene, Dermira, Eli-Lilly, Forward Pharma, Genentech, GlaxoSmithKline, Janssen, Kyowa Hako Kirin, Kythera, Leo Pharma, Merck and Co, Merck-Serono, Novartis, Pfizer, Regeneron, Rigel, Roche, Sanofi-Genzyme, Takeda, UCB, Valeant, Xenon, and Xoma., Consultant for: Amgen, Anacor, AbbVie, Active Biotech, Allergan, Astellas, AstraZeneca, Basilea, Bayer, Biogen-Idec, BMS, Boehringer-Ingelheim, CanFite, Celgene, Dermira, Eli-Lilly, Forward Pharma, Genentech, GlaxoSmithKline, Janssen, Kyowa Hako Kirin, Kythera, Leo Pharma, Merck and Co, Merck-Serono, Novartis, Pfizer, Regeneron, Rigel, Roche, Sanofi-Genzyme, Takeda, UCB, Valeant, Xenon, and Xoma., Speakers bureau: Amgen, Anacor, AbbVie, Active Biotech, Allergan, Astellas, AstraZeneca, Basilea, Bayer, Biogen-Idec, BMS, Boehringer-Ingelheim, CanFite, Celgene, Dermira, Eli-Lilly, Forward Pharma, Genentech, GlaxoSmithKline, Janssen, Kyowa Hako Kirin, Kythera, Leo Pharma, Merck and Co, Merck-Serono, Novartis, Pfizer, Regeneron, Rigel, Roche, Sanofi-Genzyme, Takeda, UCB, Valeant, Xenon, and Xoma., M. Gooderham Grant/research support from: AbbVie, Amgen, Boehringer Ingelheim, Celgene, Coherus, Dermira, Galderma, GSK, Jansen, Leo Pharma, Lilly Medimmune, Merck Serono, Novartis, Regeneron, Roche, Sanofi Genzyme, Takeda, UCB, Pfizer, and Valeant., Consultant for: AbbVie, Amgen, Boehringer Ingelheim, Celgene, Coherus, Dermira, Galderma, GSK, Jansen, Leo Pharma, Lilly Medimmune, Merck Serono, Novartis, Regeneron, Roche, Sanofi Genzyme, Takeda, UCB, Pfizer, and Valeant., Speakers bureau: AbbVie, Amgen, Boehringer Ingelheim, Celgene, Coherus, Dermira, Galderma, GSK, Jansen, Leo Pharma, Lilly Medimmune, Merck Serono, Novartis, Regeneron, Roche, Sanofi Genzyme, Takeda, UCB, Pfizer, and Valeant., Y. Zhao Employee of: Sun Pharmaceuticals, S. Lowry Employee of: Sun Pharmaceuticals, A. Mendelsohn Employee of: Sun Pharmaceuticals, J. Parno Employee of: Sun Pharmaceuticals, Q. Li Employee of: Merck and Co., Inc., C. Rosa Employee of: Merck and Co., Inc., K. Reich Grant/research support from: Abbvie, Amgen, Biogen-Idec, Celgene, Centocor, Covagen, Forward Pharma, GlaxoSmithKline, Janssen-Cilag, Leo, Lilly, Medac, Merck and Co, Novartis, Pfizer, Vertex, and Takeda., Consultant for: Abbvie, Amgen, Biogen-Idec, Celgene, Centocor, Covagen, Forward Pharma, GlaxoSmithKline, Janssen-Cilag, Leo, Lilly, Medac, Merck and Co, Novartis, Pfizer, Vertex, and Takeda., Speakers bureau: Abbvie, Amgen, Biogen-Idec, Celgene, Centocor, Covagen, Forward Pharma, GlaxoSmithKline, Janssen-Cilag, Leo, Lilly, Medac, Merck and Co, Novartis, Pfizer, Vertex, and Takeda.